The Effectiveness of Digital Samsat Services in Increasing Motor Vehicle Tax (PKB) Payment Compliance at the Wajo Samsat Revenue Technical Implementation Unit, Wajo Regency - Sitti Aminah; Asrijal Asrijal; Muh. Rifki Aswar (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the effectiveness of Digital Samsat Services in increasing taxpayer compliance in paying Motor Vehicle Tax (PKB), as well as to identify the supporting and inhibiting factors in its implementation at the Wajo Samsat Revenue Technical Implementation Unit (UPT), Wajo Regency. This study employed a descriptive qualitative approach to obtain an in-depth understanding of the service implementation process and taxpayer responses. Data were collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, consisting of Wajo Samsat administrators, representatives of related agencies, and taxpayers in Wajo Regency. Data analysis was conducted using an interactive model that included data collection, data condensation, data presentation, and conclusion drawing. The results indicate that Digital Samsat Services in Wajo Regency have been implemented effectively. This is reflected in several indicators, including faster service delivery, improved administrative efficiency, better system integration, and easier access for taxpayers. Digital services also encourage taxpayers, particularly technology-literate users, to fulfill their tax obligations more conveniently and on time. However, implementation still faces obstacles, such as limited digital literacy, uneven internet access, and the need for wider public socialization.